Comparative effectiveness of second-line immune checkpoint inhibitor therapy versus chemotherapy for malignant pleural mesothelioma. (September 2021) - Kim, Roger Y.; Li, Yimei; Marmarelis, Melina E.; Vachani, Anil
Highlights: Immune checkpoint inhibitor (ICI) therapy is commonly used in the second line setting in patients with mesothelioma. Among real-world patients with mesothelioma, second-line ICI therapy improved overall survival compared to chemotherapy. Our findings are in contrast with a recent clinical trial, highlighting the importance of real-world evidence. Abstract: Objectives: Second-line immune checkpoint inhibition (ICI) was recently shown to have a survival advantage over placebo in malignant pleural mesothelioma (MPM), but the survival comparison to chemotherapy in patients with MPM receiving routine clinical care is unknown. Our objective was to examine the effectiveness of second-line ICI versus chemotherapy on overall survival (OS) outcomes in real-world patients with advanced MPM. Materials and Methods: We performed a multicenter retrospective cohort study of real-world adult patients with advanced MPM who received first-line platinum-based chemotherapy and at least two total lines of systemic therapy. Patients received either second-line chemotherapy (gemcitabine and/or vinorelbine) or ICI therapy (pembrolizumab or nivolumab ± ipilimumab). The primary outcome was OS, defined as the time from second-line therapy initiation to death or end of the observation period. We used Kaplan-Meier methods and Cox proportional hazards modeling with adjustment for relevant patient demographic and clinical variables to compare OS between the two second-line treatment groups. Results: Of the 176 patients with MPM, the median age was 75 years (IQR: 69–79.5 years), and most were white (77%), male (74%), and had epithelioid histology (67%). Thirty-five percent (61) received second-line chemotherapy and 65% (1 1 5) ICI therapy (80 pembrolizumab, 31 nivolumab, and 4 nivolumab + ipilimumab). Treatment with ICI was associated with significantly longer median OS compared to chemotherapy (8.7 vs 5.0 months, p=0.001; adjusted hazard ratio: 0.52, 95% CI: 0.34–0.81). The estimated 12-month OS probability was 36.7% (95% CI: 27.6%-45.8%) and 15.6% (95% CI: 7.7%-26.1%) in the ICI and chemotherapy groups, respectively. Conclusion: In this "real-world" population of patients with MPM, treatment with ICI was associated with improved OS outcomes compared to chemotherapy in the second-line setting, in contrast with a recent clinical trial. Our findings suggest that ICI may benefit patients with advanced MPM and progression after initial platinum-based chemotherapy.